Juridical Review Selling and Purchasing House in The Public Housing Credit (KPR) Process Based on Law No. 1 of 2011 Concerning Housing and Settlement Area (Study at PT. State Savings Bank Baubau Branch) - Rizki Mustika Suhartono; Ernawati Ernawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
This research was conducted to find out the juridical review of selling and buying houses in the public housing credit (kpr) process based on law no. 1 of 2011 concerning housing andsettlement area pt. state savings bank baubau branc.This study uses an empirical juridical method. Researchers used instrument observation, interviews and documentation. From the results of the research, the legal consequences of transferring the debtor underhanded in the housing loan agreement (KPR-BTN) and the efforts taken by the bank to overcome it, selling mortgage houses underhanded by debtors who have not paid off their debts, is an unlawful act because The KPR house is a collateral object for the debtor's debt to the Bank, so that the Bank can sue the debtor to provide compensation for cancellation of the sale and purchase of KPR houses by the old debtor which was carried out underhand and immediately pay off all the remaining debt. The sale of KPR houses under the hands of the Debtor does not eliminate the Debtor's obligation to pay off his debts to the Bank. It is suggested that in order to avoid problems that arise in the future, people who want to transfer their debtors to KPR BTN can do so after obtaining approval from the bank as the creditor.